1999
DOI: 10.1029/1999jd900764
|View full text |Cite
|
Sign up to set email alerts
|

A hierarchical approach for the regionalization of precipitation annual maxima in Canada

Abstract: Abstract. The L moments are used in the three stages of regional frequency analysis: the delineation of homogeneous regions, the identification of a regional parent distribution, and the estimation of distribution parameters. Numerical analysis is conducted on 5 min to 24 hours annual rainfall extremes from 375 precipitation gaging stations in Canada. The numerical analysis concluded that Canada could be considered as a single homogeneous region in which the L skewness and L kurtosis display no significant spa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
88
1
15

Year Published

2002
2002
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 109 publications
(115 citation statements)
references
References 24 publications
(22 reference statements)
9
88
1
15
Order By: Relevance
“…This assumption contrasts with the findings of other studies, which show that the statistics of rainfall extremes vary systematically with location Alila, 1999;Brath et al, 2003). These studies also identified statistically significant relationships between these statistics and the mean annual precipitation (MAP), which was used as a surrogate of geographical location.…”
Section: Introductioncontrasting
confidence: 54%
See 4 more Smart Citations
“…This assumption contrasts with the findings of other studies, which show that the statistics of rainfall extremes vary systematically with location Alila, 1999;Brath et al, 2003). These studies also identified statistically significant relationships between these statistics and the mean annual precipitation (MAP), which was used as a surrogate of geographical location.…”
Section: Introductioncontrasting
confidence: 54%
“…The study described in this paper investigates the applicability of the findings of and Alila (1999) in a large geographical area of northern central Italy. The analysis considers annual series of precipitation maxima for storm duration from 15 min to 1 day that were observed by a dense raingauge network.…”
Section: Growth Factor Estimationmentioning
confidence: 99%
See 3 more Smart Citations